The use of single oxen for crop cultivation in Ethiopia - Gryseels, Guido; Astatke, A.; Anderson, F.M.; Asamenew, G. (International Livestock Centre for Africa, 1984)
Reports experiences with on-farm trials to assess the use of single oxen for work on mixed smallholder farms in the central highlands of Ethiopia, with particular reference to draft power and agricultural production, design and testing of the single ox technique, and results obtained during the 1983 crop year and future prospects with respect to feed requirements and advantages of using the single ox.